Does the righting behaviour effectively reflect stress in Arbacia dufresnii Arbacioida: Arbaciidae)? - Chaar, Florencia (2024)
Introduction: Righting behaviour has been used as a health indicator in response to stressor variables. Using this parameter in aquaculture could help to reduce mortality and improve welfare in the sea urchin Arbacia dufresnii culture. Objective: The purpose of this study was to determine the effect of sex, diameter, and three stressor factors on the righting behaviour of the sea urchin A. dufresnii. Methods: A total of 300 animals were evaluated for complete righting behaviour (CRB) time, with 100 of them also recording half righting behaviour (HRB) time. Three stressors were applied to the animals: serial repetitions (three successive turnings), temperature (24-hour shock), and spawning induction with KCl injection. A stopwatch was used to record the time, and a precision calliper was used to measure the diameter. Results: Righting time was discovered to be diameter dependent but sex independent. The upper temperature limit of 19 °C had a significant effect on righting behaviour compared to 16 °C and 13 °C with CRB times up to 150 seconds.  Serial repetitions and spawning had no significant effect. However, based on the recorded times, it can be deduced that spawning had an effect on the health of the animals, with CRB times of up to 150 seconds compared to the control, with lower times. Conclusions: Complete righting behaviour appears to be an optimal indicator for evaluating the health and condition of the sea urchin A. dufresnii, but more tests would be performed to confirm the effect of the control treatment on post-spawning stress.